The Effect of Money Supply on Exchange Rate in ASEAN-5: Empirical Test of Dornbusch Overshooting Model - Maghfiroh, Ulil; Jayadi, Akhmad; Dumauli, Magdalena Triasih (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
The primary purpose of this study is to analyze the effects of the money supply on exchange rates in ASEAN-5 and whether there is an exchange rate overshooting phenomenon with the application of the Dornbusch Overshooting Model. This study uses the Autoregressive Distributed-Lag (ARDL) method to analyze the short and long-term effects and uses time series data from 1980 to 2021 in ASEAN-5. The results of this study are still ambiguous in finding the overshooting phenomenon in ASEAN-5. In the short term, the research results support overshooting in two countries, Malaysia and Thailand. However, in the long term, no positive and significant influence was found between the money supply gap and exchange rate misalignment in ASEAN-5. Besides that, the inflation gap, interest rate gap, and output gap also greatly influence changes in exchange rate misalignment and have different significant effects in the short and long term.